Recent advances in nanostructured electrocatalysts for seawater electrolysis: Towards sustainable hydrogen production - Muhammad Atif Daniel, Aziz; Sakinah, Muhamad Hisham; Norazlianie, Sazali; Junaidi, Afdhal; Kadirgama, Kumaran (Penerbit UMP, 2025)
Seawater electrolysis has emerged as a promising and sustainable method for large-scale hydrogen production, utilizing abundant seawater as an alternative to freshwater electrolysis. However, challenges such as catalyst degradation, chloride-induced corrosion, and competition between the oxygen evolution reaction (OER) and chlorine evolution reaction (CER) hinder its widespread adoption. Recent advancements in nanostructured electrocatalysts, including metal-organic frameworks (MOFs), single-atom catalysts (SACs), and transition metal-based alloys, have significantly improved catalytic efficiency, reduced overpotentials, and enhanced stability in harsh marine environments. This review provides a comprehensive analysis of the latest breakthroughs in nanostructured electrocatalysts for seawater electrolysis, with a focus on key material innovations such as nickel-based alloys, molybdenum carbide/phosphide hybrids, and multi-component catalysts optimized for hydrogen evolution reaction (HER) kinetics. Additionally, the role of computational modeling and machine learning in accelerating catalyst design is explored. The economic feasibility and environmental impact of these advanced materials are critically assessed, considering lifecycle analysis, resource sustainability, and industrial scalability. Furthermore, the integration of seawater electrolysis with renewable energy sources, such as offshore wind and solar power, along with hydrogen storage and CO₂ capture strategies, is examined to highlight its potential for a carbon-free energy future. Despite significant progress, challenges remain in enhancing long-term catalyst durability, reducing costs, and achieving large-scale implementation. This review contributes to the ongoing development of sustainable hydrogen production technologies, reinforcing the pivotal role of seawater electrolysis in the global transition toward clean energy.